Recurrent Encephalopathy and Severe Anion Gap Metabolic Acidosis in a Patient with Short Bowel: It Is D-Lactic Acidosis - Avni Jain; Kiran Jhinger; Jonathon Bellas (Case Reports in Gastroenterology, 2021)
D-lactic acidosis is a rare and potentially underrecognized condition in patients with short bowel syndrome. We present the case of a 61-year-old female with a history of an ileojejunal bypass at age 18 who presented to hospital with acute-onset encephalopathy, ataxia, and severe anion gap metabolic acidosis (AGMA). On initial investigations there were no identifiable etiologies for the AGMA. Further history revealed that she had been experiencing these symptoms on a recurrent basis for the past 40 years. An oral carbohydrate load was given to the patient in hospital which reproduced her symptoms and the AGMA. A serum D-lactate level returned elevated several weeks later. A 2-month follow-up revealed that all her symptoms had ceased with limitation of carbohydrates to 150 g per day. Patients with short bowel syndrome are susceptible to developing D-lactic acidosis due to the large carbohydrate loads that are delivered to the colon, where they are then metabolized. Due to its rarity, it is likely that there is a delay in recognition of this condition. This case report describes a common clinical presentation of this rare condition and describes the pathophysiology, diagnosis, and management of D-lactic acidosis in small bowel syndrome.